2007
DOI: 10.2533/chimia.2007.373
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacterial Natural Products for the Inhibition of Biofilm Formation and Biofouling

Abstract: Biofouling is defined by the non-specific attachment of biological material (proteins, carbohydrates, prokaryotic cells and higher organisms) to surfaces upon their exposuret oa ny biological fluid. Biofouling is a serious problem in many areas ranging from marine technology,nuclear power plants, dentistry,food processing to biomedical implants. This process can be addressed either actively by chemical compounds inhibiting growth, settlement or biofilm formation, or passively by generating repellent or resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…(78-12A) and other cyanobacteria to be promising sources of lead compounds for the development of new drugs and pesticides/insecticides (as reviewed for other natural acetylcholineesterase inhibitors, Houghton et al 2006) or novel antifouling agents (reviewed in Gademann 2007).…”
Section: Time [Min]mentioning
confidence: 99%
“…(78-12A) and other cyanobacteria to be promising sources of lead compounds for the development of new drugs and pesticides/insecticides (as reviewed for other natural acetylcholineesterase inhibitors, Houghton et al 2006) or novel antifouling agents (reviewed in Gademann 2007).…”
Section: Time [Min]mentioning
confidence: 99%
“…A promising strategy to combat biofouling is the generation of surfaces which are resistant or inert to this process (Yebra et al 2004;Gademann 2007). To this end, several antifouling polymers such as polyethylene glycol (PEG) (Desai and Hubbell 1991;Lee et al 1989;Prime and Whitesides 1991), polyglycerol (Siegers et al 2004), poly(ethyleneoxide)-poly(propyleneoxide)/pluronics (Lee et al 2000;Marsh et al 2002), peptoids (Statz et al 2005) and poly-2-methyl-2-oxazoline (Konradi et al 2008) have been developed.…”
Section: Preparation Of Anachelin Chromophorementioning
confidence: 99%
“…The organism could act on cyanide at a highly alkaline pH of 11.5. All of these studies have shown that due to their key role in the iron cycle, siderophores have attractive potential for development and advancement of therapeutic drugs [56], inhibition of biofilm formation [70], and bioremediation [105].…”
Section: Siderophoresmentioning
confidence: 99%